Cyclometalated Ruthenium(II) Anthraquinone Complexes Exhibit Strong Anticancer Activity in Hypoxic Tumor Cells. Issue 43 (4th September 2015) - Zeng, Leli; Chen, Yu; Huang, Huaiyi; Wang, Jinquan; Zhao, Donglei; Ji, Liangnian; Chao, Hui
Abstract Hypoxia is the critical feature of the tumor microenvironment that is known to lead to resistance to many chemotherapeutic drugs. Six novel ruthenium(II) anthraquinone complexes were designed and synthesized; they exhibit similar or superior cytotoxicity compared to cisplatin in hypoxic HeLa, A549, and multidrug‐resistant (A549R) tumor cell lines. Their anticancer activities are related to their lipophilicity and cellular uptake; therefore, these physicochemical properties of the complexes can be changed by modifying the ligands to obtain better anticancer candidates. Complex 1, the most potent member of the series, is highly active against hypoxic HeLa cancer cells (IC50=0.53 μM). This complex likely has 46‐fold better activity than cisplatin (IC50=24.62 μM) in HeLa cells. This complex tends to accumulate in the mitochondria and the nucleus of hypoxic HeLa cells. Further mechanistic studies show that complex 1 induced cell apoptosis during hypoxia through multiple pathways, including those of DNA damage, mitochondrial dysfunction, and the inhibition of DNA replication and HIF‐1α expression, making it an outstanding candidate for further in vivo studies.